2022
DOI: 10.3390/ijerph19073801
|View full text |Cite
|
Sign up to set email alerts
|

Association between Drinking Patterns and Incident Hypertension in Southwest China

Abstract: Based on a prospective cohort study of adults from southwest China with heterogeneity in their demographical characteristics and lifestyles, we aimed to explore the association between drinking patterns and incident hypertension under the interaction of these confounding factors. The Cox proportional hazard model was used to estimate the hazard ratios (HR) and 95% confidence intervals (95% CI). Subgroup analysis was performed according to sex, ethnicity, area, occupation, smoking, and exercise to compare the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 46 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…Participants with type 2 diabetes (T2DM) at baseline or previously were considered to have a history of diabetes. Criteria for type 2 diabetes and physical activity have been reported in the previous literature ( 20 ). Height and weight of each participant were collected by trained physicians with an accuracy of 0.001 m and 0.1 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with type 2 diabetes (T2DM) at baseline or previously were considered to have a history of diabetes. Criteria for type 2 diabetes and physical activity have been reported in the previous literature ( 20 ). Height and weight of each participant were collected by trained physicians with an accuracy of 0.001 m and 0.1 kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The venous blood of participants was sampled after fasting for at least 8 h to obtain the blood biochemical 10.3389/fcvm.2023.1027988 indicators, including total cholesterol (TC), triglyceride (TG), highdensity lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). Based on the questionnaire, we calculated the average daily ethanol intake of the participants as described in the previous report (20), and divided participants into four groups: non-drinking (0 g/d), light drinking (0-12 g/d), moderate drinking (12-24 g/d), heavy drinking (> 24 g/d).…”
Section: Covariatesmentioning
confidence: 99%
“…Meanwhile, men consumed alcohol in larger amounts and more frequently than women ( 31 ). After stratifying by sex, daily drinking increased the risk of hypertension in men but did not affect women in Southwest China ( 32 ). A J-shaped relationship between alcohol consumption and hypertension has been identified in women, while alcohol consumption was linearly correlated with the risk of hypertension in men ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Smokers were also at an increased odds of drinking alcohol irrespective of gender [ 23 , 25 , 28 ]. Additionally, smoking and drinking concurrently also elevated the risk of hypertension [ 29 , 30 ]. Another study found that the proportion of smokers among drinkers was high [ 30 ], which was also consistent with our study findings where the prevalence of smokers among current drinkers was 19.2%.…”
Section: Discussionmentioning
confidence: 99%